The Molecular Mechanisms Underlying Mitochondria-Associated Endoplasmic Reticulum Membrane-Induced Insulin Resistance - Cheng, Han; Gang, Xiaokun; He, Guangyu; Liu, Yujia; Wang, Yingxuan; Zhao, Xue; Wang, Guixia (Frontiers in Endocrinology, 2020)
Mitochondria and the endoplasmic reticulum (ER) are connected at multiple sites via what are known as mitochondria-associated ER membranes (MAMs). These associations are known to play an important role in maintaining cellular homeostasis. Impaired MAM signaling has wide-ranging effects in many diseases, such as obesity, diabetes, and neurodegenerative disorders. Accumulating evidence has suggested that MAMs influence insulin signaling through different pathways, including those associated with Ca2+ signaling, lipid metabolism, mitochondrial function, ER stress responses, and inflammation. Altered MAM signaling is a common feature of insulin resistance in different tissues, including the liver, muscle, and even the brain. In the liver, MAMs are key glucose-sensing regulators and have been proposed to be a hub for insulin signaling. Impaired MAM integrity has been reported to disrupt hepatic responses to changes in glucose availability during nutritional transition and to induce hepatic insulin resistance. Meanwhile, these effects can be rescued by the reinforcement of MAM interactions. In contrast, several studies have proposed that enhanced ER-mitochondria connections are detrimental to hepatic insulin signaling and can lead to mitochondrial dysfunction. Thus, given these contradictory results, the role played by the MAM in the regulation of hepatic insulin signaling remains elusive. Similarly, in skeletal muscle, enhanced MAM formation may be beneficial in the early stage of diabetes, whereas continuous MAM enhancement aggravates insulin resistance. Furthermore, recent studies have suggested that ER stress may be the primary pathway through which MAMs induce brain insulin resistance, especially in the hypothalamus. This review will discuss the possible mechanisms underlying MAM-associated insulin resistance as well as the therapeutic potential of targeting the MAM in the treatment of type 2 diabetes.